First DNA Barcoding Records of Fish Species from Totok and Makalo Estuaries, North Sulawesi, Indonesia - Febry Susane Ivonne Menajang; Ari Berty Rondonuwu; Alex Denny Kambey; Rene Charles Kepel (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
The Totok and Makalo River estuaries in North Sulawesi, Indonesia, serve as vital habitats teeming with fish biodiversity, supporting coastal ecosystems and local fisheries. This study aimed to identify fish species and elucidate their genetic relationships through DNA barcoding of the Cytochrome Oxidase I (COI) gene. Fish samples were collected from both estuaries using nets and traps, followed by molecular analysis involving polymerase chain reaction (PCR) amplification and Sanger sequencing. The results confirmed the presence of 11 fish species, including Osteomugil engeli, Polydactylus plebeius, and Gazza minuta, with high identification accuracy (over 98% sequence similarity to reference databases). Notably, Paracentropogon rubripinnis and Nematalosa come were recorded for the first time in North Sulawesi waters, expanding the known distribution of these species. Significant genetic variation was detected in P. rubripinnis, potentially indicating cryptic speciation or local adaptation to environmental gradients. Phylogenetic analysis revealed close genetic affinities between certain species and populations from Taiwan and Bangladesh, suggesting historical migration patterns or shared ancestry, possibly facilitated by ocean currents. These findings underscore the rich genetic diversity in these estuaries, which are influenced by factors like salinity, temperature, and anthropogenic pressures. The study emphasizes the urgency of conservation strategies, including habitat protection and sustainable fishing practices, to preserve biodiversity and maintain ecosystem services. By providing baseline data on species composition and genetic connectivity, this research contributes to broader efforts in marine biodiversity monitoring and informs policy for coastal management in Indonesia's biodiversity hotspots.